An Upper Maastrichtian ammonite faunule from the Eastern Desert, Egypt - Kennedy, W; Kulbrok, F (2003)
An ammonite faunule of Pseudophyllites indra (FORBES, 1846), Eubaculites simplex (KOSSMAT, 1895), and Discoscaphites kambysis (QUAAS, 1902), is described from the upper part of the Gansserina gansseri planktonic foram Zone/CC 25c nannofossil Zone of the St. Anthony Formation at the Monastery of St. Anthony in the Eastern Desert, Egypt. An Upper, but not uppermost Maastrichtian horizon is assigned to the assemblage, none of the constituent species of which have been recorded previously from the Egyptian Upper Cretaceous. © 2003 E. Schweizerbart'sche Verlagsbuchhandlung.